Cultural Competence in Refugee Service Settings: A Scoping Review (Mary Ann Liebert, 2021)
Purpose: Refugees and asylum seekers have unique and complex needs related to their experiences of forced displacement and resettlement. Cultural competence is widely recognized as important for the provision of effective and equitable services for refugee populations. However, the delivery of culturally appropriate services?including health care and social services?is often complicated by unclear definitions and operationalization of cultural competence. Further, the unique needs and priorities of people from refugee backgrounds are under-addressed in the cultural competence literature. This scoping review seeks to synthesize the peer-reviewed literature examining cultural competence in refugee service settings. Methods: A systematic search of four databases (EBSCO, Proquest, Scopus and Google Scholar) identified 26 relevant peer-reviewed studies for analysis. Results: A range of approaches to cultural competence were identified at the level of individual providers and organizations. Conclusion: We identified a need for greater refugee participation and perspectives in the practice of cultural competence, increased conceptual clarity and greater recognition of structural barriers. We call for further rigorous research that critically examines the concept of cultural competence and its meaning and relevance to refugee populations.